2011
DOI: 10.1021/jf202781v
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Variability in Conventional and Glyphosate-Tolerant Soybean (Glycine max L.) Varieties Grown in Different Regions in Brazil

Abstract: The compositions of a diverse range of commercially available conventional and genetically modified (GM; glyphosate-tolerant) soybean varieties from maturity groups 8 and 5, respectively, grown in the northern and southern soybean regions of Brazil during the 2007-2008 and 2008-2009 growing seasons were compared. Compositional analyses included measurement of essential macro- and micronutrients, antinutrients, and selected secondary metabolites in harvested seed as well as measurement of proximates in both for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 14 publications
4
28
0
Order By: Relevance
“…The secondary metabolites of TS and OS are not different (Zhou et al, 2011). However, Lappé et al reported lower levels of phytoestrogens in TS than in OS.…”
Section: Discussionmentioning
confidence: 93%
“…The secondary metabolites of TS and OS are not different (Zhou et al, 2011). However, Lappé et al reported lower levels of phytoestrogens in TS than in OS.…”
Section: Discussionmentioning
confidence: 93%
“…Changes to other physiological mechanisms, such as photosynthesis and other biosynthetic processes leading to biomass accumulation result from glyphosate use and directly affect soybean yield components (Zobiole et al, 2010d. The presence of any symptom is clear related to the glyphosate application, as GMOs proved to have the same compositional variability as conventional soybean in different regions in Brazil (Zhou et al, 2011).…”
Section: Effectsmentioning
confidence: 99%
“…These programs have involved measurement of key components such as isoflavones from different 40-3-2 varieties (the event crossed into various commercial genetic backgrounds of different maturity classes) grown across diverse geographical regions. McCann et al (2005) and Zhou et al (2011a) Because it is typical for nutrients and anti-nutrients in crops to vary depending on variety (genetic background), the environmental conditions and cultivation method used (Setchell & Cole, 2003;De Mejia et al, 2003;Zhou et al, 2011b), and the glyphosate-tolerant and control soybeans in these studies were not matched for genetic background and were grown under different environmental conditions (not grown at the same field trial site during the same season), the studies were not appropriately designed to compare whether the introduction of the glyphosate tolerant trait in the soybean had resulted in altered levels of isoflavones. Nevertheless, the study indicates that the isoflavone composition of commercialised glyphosate-tolerant soybeans over several years of breeding into multiple genetic backgrounds remains substantially equivalent to that of conventional soybeans.…”
Section: Genetically Modified Soybeansmentioning
confidence: 99%
“…It was noted that the magnitude of the differences for daidzein and glycitein was very small (7.5-10.6% relative to the control), that the level of genistein did not differ, and that all values were within the range normally observed in conventional soybeans (subsection Conventional soybeans in section 3.1.7 Isoflavones in legumes). An extensive variation in isoflavone levels was demonstrated in a study performed in two regions of Brazil over two growing seasons (Zhou et al, 2011b). This study evaluated the relative contribution of growing season, growing region, phenotype (glyphosate tolerance due to the MON 89788 event vs. sensitivity), and genotype (genetic background of cultivar) on variability.…”
Section: Genetically Modified Soybeansmentioning
confidence: 99%